European Organizations (London, 1959)
This report is the work of a Research Group with an inter Tnational membership which has met regularly at PEP from September 1956 to December 1958. The Group wishes to acknow ledge the help and assistance it has received in carrying out its work from a variety of sources. Particular thanks are due to the members of the secretariats of various institutions and others who have given freely of their time in discussing the activities of their organisations with members of the research staff and in reading group papers submitted to them.
Keywords: Economics